Whole-genome sequencing-based species classification, multilocus sequence typing, and antibiotic resistance mechanisms of the clinical Aeromonas complex - Lu, Junwan; Zhang, Lei; Yan, Chunxia; Lin, Naru; Zhang, Yuan; Sha, Yuning; Zhao, Jingxuan; Lu, Jun; Bao, Qiyu; Zhang, Guozhi (Frontiers in Microbiology, 2025)
BackgroundMultidrug-resistant strains of the genus Aeromonas can produce various β-lactamases that confer resistance to a broad spectrum of β-lactams, which poses a significant public health threat due to their emergence and spread in clinical settings and natural environments. Therefore, a comprehensive investigation into the antibiotic resistance mechanisms of Aeromonas is scientifically significant.MethodsBetween 2018 and 2021, 78 clinical Aeromonas isolates were collected from human clinical specimens. The MicroScan WalkAway system and average nucleotide identity (ANI) analyses were used to classify the bacterial species. Antibiotic susceptibility was determined through the minimum inhibitory concentration (MIC) test via the agar dilution method. To determine the resistance mechanism and the structure of the resistance gene-related sequences, molecular cloning, whole-genome sequencing and bioinformatic analysis were performed.ResultsAmong the 78 Aeromonas isolates studied in this work, obtained from various specimens from different clinical departments, 77 were classified into seven known species by ANI analysis. Most of the isolates were A. caviae (34.6%, 27/78), followed by A. hydrophila (25.6%, 20/78). Multilocus sequence typing (MLST) revealed that they belonged to 72 sequence types (STs), including 52 new STs. A total of 334 resistance genes of 30 antibiotic resistance genotypes were identified from the genomes, more than half (55.99%, 187/334) of which were β-lactamase genes. The isolates showed much higher rates of resistance to penicillins (penicillin G, 98.7%) and first-generation cephalosporins (cefazolin, 96.2%), but lower resistance rates to fourth-generation cephalosporins (cefepime, 6.4%), monobactams (aztreonam, 5.1%), and carbapenems (imipenem, 1.3% and meropenem, 5.1%). Structural analyses of some β-lactamase genes (such as blaNDM-1 and blaPER-3) related sequences revealed that they were generally associated with mobile genetic elements.ConclusionThe investigation of the correlation between the distribution of β-lactamase genes and Aeromonas resistance phenotypes in this study suggested an urgent need for rigorous monitoring and control to counteract the escalating public health threat posed by the increase in Aeromonas strains harboring extended-spectrum β-lactamase and metallo-β-lactamase genes.